Extreme electromagnetic rotation, chemical reaction, Hall and ion slip effects on weakly ionized fluid in a Riga channel - M. Veera Krishna; E. Rajasekhar (Results in Engineering, 2024)
The utilization of external magnetic or electric fields, particularly through a Riga setup, markedly enhances flow dynamics by mitigating frictional forces and turbulent fluctuations, thereby facilitating superior flow management. Such improvements are especially beneficial in optimizing the operational efficiency of machinery and turbines. Our research focuses on the behaviour of a weakly ionized fluid within a porous, infinitely extended Riga channel (or electromagnetic channel) set in a rotational frame work affected by Hall and ion-slip electric fields. This model integrates the cumulative repulsions of an abruptly apply pressure gradients, electro-magnetic force, electromagnetic radiation, as well as chemical reactions. The physical configuration of the model features a stationary RHS wall as well as the LHS wall subjected to transversal vibration, establishing a complex flow environment. This circumstance is analytically modeled utilizing time dependent PDE, with the Laplace transform method applied to achieve a closed-format resolution for the course controlling equations. Through detailed graphical and tabular data, the investigations explored the impacts of assorted pivotal parameters on the model's flow traits and quantities. Our results indicate that an upswing in the modified Hartmann number significantly enhances fluids flow in the conduit, with the most important resultant flow showing marked improvement as Hall and ion-slip parameters amplify, and secondly the resultant flow diminishing chemical reaction parameter. Additionally, species concentration lowers with higher Schmidt numbers and chemical reaction rates, while an expanded modified Hartmann number correlate with enhanced shear stress near the conduit wall. Moreover, an elevation in the radiating parameter reduces the rate of temperature transport at the vibrating wall, whereas this at the stationary wall improves. This study has profound implications across several fields, notably in fusion energy research, spacecraft propulsion systems, satellite operations, aerospace engineering, and advanced manufacturing technologies.